Analysis of Factors Affecting Financial Distress With Intelectual Capital as Moderation (Case Analysis of Retail Companies in 2017-2020) - Dessy Ambarsari; Triyono Triyono; Andy Dwi Bayu Bawono (Cita Konsultindo Research Center, 2022)
This research aimed to find out factors affecting financial distress, and how intellectual capital capabilities and moderate the factors affecting financial distress. The main difference was intellectual capital usage as a moderation variables that has never been used in previous studies. This study used MRA with SPSS 26.0 as an analysis tool. The sample used in this study was retail companies listed on the IDX in the 2017-2020 of 72 companies. The analysis results showed that profitability, liquidity, leverage, and sales growth have a negative and significant on financial distress and intellectual capital moderating the effect of profitability, liquidity, leverage, and sales growth on financial distress both partially and jointly